The Use of English Songs to Improve Students’ Listening Skills at SMPN 2 Abang - Ni Dwi (Pubmedia Jurnal Pendidikan Bahasa Inggris, 2026)
Listening is one of the most essential skills in learning English, especially for students in English Foreign Language (EFL) contexts. However, many students face difficulties in understanding spoken English due to limited exposure to authentic language and a lack of motivation during listening activities. This research aims to investigate the use of English songs as a learning medium to improve students’ listening skills, identify the types of songs that are most effective, and examine students’ responses toward song-based listening activities. This study employed a quantitative descriptive research design and involved 30 seventh-grade students of SMP Negeri 2 Abang. Data were collected through a questionnaire administered after students participated in listening activities using English songs. The questionnaire focused on students’ experiences, preferences, motivation, and perceptions related to listening practice through songs. The collected data were analyzed using descriptive statistics, including frequency, percentage, mean, and standard deviation. The results of the study show that the majority of students had positive attitudes toward the use of English songs in listening lessons. Most students agreed that English songs helped them improve their understanding of pronunciation, vocabulary, intonation, and overall listening comprehension. Students also reported higher motivation and enjoyment when learning through songs compared to traditional textbook audio materials. In addition, slow-tempo songs with clear lyrics were found to be the most effective, while fast or unclear songs caused some difficulties for students. In conclusion, English songs are an effective and engaging tool for improving students’ listening skills. Therefore, English teachers are encouraged to integrate suitable English songs into listening activities with appropriate guidance to create a more enjoyable and effective learning environment.